2013
DOI: 10.4308/hjb.20.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Fungal Communities in Tempeh as Reveal by Amplified Ribosomal Intergenic Sequence Analysis

Abstract: Tempeh is an Indonesian traditional fermented food produced using Rhizopus as a starter culture. In practice, however, the starter culture as well as fermentation processes would yield a polymicrobial fermentation, which generated a unique tempeh flavor and texture. This condition makes Indonesian tempeh as one of the most complex fermented food, while at the same time would make it difficult to scale up tempeh production with uniform quality and consistency. The aim of this study was to compare a number of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…This is aligned with the results of previous studies on fermented food [21, 22]. Zhou et al [23] also found that probiotic-rich fermented food consumption increased overall cognitive function, although the effects vary according to ethnic groups [22]. A study by Hogervorst et al [10] reported that tempeh consumption was associated with increased immediate recall scores among older people.…”
Section: Discussion/conclusionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is aligned with the results of previous studies on fermented food [21, 22]. Zhou et al [23] also found that probiotic-rich fermented food consumption increased overall cognitive function, although the effects vary according to ethnic groups [22]. A study by Hogervorst et al [10] reported that tempeh consumption was associated with increased immediate recall scores among older people.…”
Section: Discussion/conclusionsupporting
confidence: 87%
“…Kridawati et al [9] reported that tempeh and tofu flour supplementation in Sprague-Dawley rats reduced their Aβ level significantly at 2- and 5-week intervals, which is not found in the casein control group [10]. These previous studies also demonstrated that both supplementation of tempeh or the intended microbiota resulted in positive effect on cognitive function [10, 23, 25, 27].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Bacterial growth during tempeh production begins in the process of soybean soaking. During the fermentation process, the producers inadvertently adding bacteria so that the bacteria eventually become an inseparable part of tempeh, and even has an important role in determining the quality of tempeh (Barus et al 2008;Seumahu et al 2013).…”
mentioning
confidence: 99%
“…Menurut Seumahu et al (2007) pada proses fermentasi tradisional ternyata dapat melibatkan banyak jenis bakteri yang kualitasnya dapat dipantau dengan melihat profil Amplified Ribosomal DNA Restriction Analysis (ARDRA) komunitas bakteri selama fermentasi Nata de coco. Dinamika yang terjadi pada komunitas bakteri dapat berpengaruh positif terhadap hasil fermentasi seperti pada tempe (Barus, 2008;Efriwati, 2013;Seumahu et al, 2013), susu dan keju (Neviani et al, 2013). Kombinasi kondisi optimum dan dinamika komunitas bakteri dapat digunakan sebagai dasar pertimbangan bagi pengembangan industri yang memproduksi selulosa dengan produktifitas dan stabilitas yang tinggi.…”
Section: Pendahuluanunclassified